Coordinate regulation of eIF2? phosphorylation by PPP1R15 and GCN2 is required during Drosophila development. - Malzer, E.; Szajewska-Skuta, M.; Dalton, L.E.; Thomas, S.E.; Hu, N.; Skaer, H.; Lomas, D.A.; Crowther, D.C.; Marciniak, S.J. (Journal of Cell Science, 2013)
Phosphorylation of eukaryotic translation initiation factor 2 alpha (eIF2?) by the kinase GCN2 attenuates protein synthesis during amino acid starvation in yeast, whereas in mammals a family of related eIF2? kinases regulate translation in response to a variety of stresses. Unlike single-celled eukaryotes, mammals also possess two specific eIF2? phosphatases, PPP1R15a and PPP1R15b, whose combined deletion leads to a poorly understood early embryonic lethality. We report the characterisation of the first non-mammalian eIF2? phosphatase and the use of Drosophila to dissect its role during development. The Drosophila protein demonstrates features of both mammalian proteins, including limited sequence homology and association with the endoplasmic reticulum. Of note, although this protein is not transcriptionally regulated, its expression is controlled by the presence of upstream open reading frames in its 5'UTR, enabling induction in response to eIF2? phosphorylation. Moreover, we show that its expression is necessary for embryonic and larval development and that this is to oppose the inhibitory effects of GCN2 on anabolic growth.